2021
DOI: 10.3390/ijerph182312376
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Inflexibility in People with Chronic Psychosis: The Mediating Role of Self-Stigma and Social Functioning

Abstract: Psychosis is associated with self-stigmatization and loss of social functioning that increase the severity of the disorder. Psychological inflexibility (PI)—an individual’s tendency to suppress undesirable private events—plays a fundamental role in the emergence and worst prognosis of psychosis. The main objective of this study was to analyze whether self-stigma and social functioning mediate the association of PI with the severity of psychosis in adults with chronic schizophrenia. The study was carried out wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Self-criticism and selfdeprecation often result in the abandonment of work, treatment and help-seeking as well as the loss of opportunities for independent living. In this sense, as has been suggested in the previous literature, people with psychosis may benefit from intervention programmes that include strategies related to self-compassion, acceptance and cognitive defusion [25,34]. Lien et al [35] found that guiding patients with a diagnosis of schizophrenia to perceive themselves more positively can effectively reduce their SS.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Self-criticism and selfdeprecation often result in the abandonment of work, treatment and help-seeking as well as the loss of opportunities for independent living. In this sense, as has been suggested in the previous literature, people with psychosis may benefit from intervention programmes that include strategies related to self-compassion, acceptance and cognitive defusion [25,34]. Lien et al [35] found that guiding patients with a diagnosis of schizophrenia to perceive themselves more positively can effectively reduce their SS.…”
Section: Discussionmentioning
confidence: 84%
“…Lien et al [35] found that guiding patients with a diagnosis of schizophrenia to perceive themselves more positively can effectively reduce their SS. Indeed, the tendency to avoid and try to get rid of negative self-evaluations has a negative impact on the social functioning of people with psychosis [25], it undermines their independence and feeds the experience of SS over and over again.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study to assess the evolution of adolescents with CHRp would help specify the relationship between variables. Fourth, the predictive model presented should be interpreted with caution, given the lack of consideration of other possible moderating or mediating variables and contextual factors, such as social isolation, stigma, family relationships, and attachment styles, that also influence the progression of the pathology (González‐Menéndez et al, 2021). Nevertheless, a large percentage of the psychopathology encountered is likely due to ER factors, in which case these nonspecific symptoms and psychological processes may act as mediators of ER risk.…”
Section: Discussionmentioning
confidence: 99%